In-Line Seawater Phosphate Detection with Ion-Exchange Membrane Reagent Delivery - Suphasinee Sateanchok (2018)
© 2018 American Chemical Society. There is an urgent need for reliable seawater phosphate measuring tools to better assess eutrophication. Today, most accepted sensing approaches are based on the established colorimetric molybdenum blue assay. It requires one to modify the sample to strongly acidic conditions and to add various reagents, principally molybdate and reducing agent (e.g., ascorbic acid), to form a blue colored phosphate complex that is subsequently detected spectrophotometrically. The associated need for large sample and mobile phase reservoirs and mixing coils are, unfortunately, not ideally adapted for the development of operationally simple in situ sensing instruments. It is here demonstrated for the first time that the key reagents needed to achieve phosphate detection by the molybdate method may be delivered by passive counter transport across ion-exchange membranes. A cation-exchange Donnan exclusion membrane placed in contact with a sample flow (450 μm thick) is shown to provide the strongly acidic conditions (pH ∼ 1) necessary for phosphate determination. Proton transport is driven, via cation-exchange, by the high sodium content of the seawater sample. Molybdate was similarly released through an anion-exchange membrane by chloride counter transport. Consequently, an in-line flow system containing the two membrane modules in series was used for delivering both hydrogen and molybdate ions into the sample to form the desired phosphomolybdate complex for subsequent spectrophotometric detection. A linear calibration in the range of 0.1-10 μM phosphate (3-300 ppb inorganic P) was achieved, which is sufficiently attractive for environmental work. A range of seawater samples was tested and the results from this membrane delivery device showed no significant differences compared to the classical molybdate assay chosen as the reference method.